2013
DOI: 10.3846/20294913.2013.837115
|View full text |Cite
|
Sign up to set email alerts
|

The Age of Clusters and Its Influence on Their Activity Preferences

Abstract: The aim of this paper is to determine whether there exist age dependent differences in the orientation of clusters’ activities. The literature depicts different approaches to the cluster evolution process, highlighting that clusters are subject to a life cycle that emphasizes different sets of activities in various stages of their development. These activities appear to follow a certain trajectory, whereby the successful completion of initial less-intensive activities stimulates a shift in focus to more demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Cluster activities cover many joint actions in areas of networking, human resources and training, research and development, marketing, internationalization, standardization, fi nancing and others (Pavelková et al, 2009;Pawliczek, Piszczur, 2013;Stejskal, 2011). Jirčíková et al (2013) in their survey of world clusters showed the most preferred activities of clusters are networking, research and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cluster activities cover many joint actions in areas of networking, human resources and training, research and development, marketing, internationalization, standardization, fi nancing and others (Pavelková et al, 2009;Pawliczek, Piszczur, 2013;Stejskal, 2011). Jirčíková et al (2013) in their survey of world clusters showed the most preferred activities of clusters are networking, research and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…iCAT In the past, monitoring was the main task of cluster managers (Tilson, 2001). Today, cluster managers are project managers (Ingstrup and Damgaard, 2013), driving shared production actively ( Jirčíková et al, 2013). Clusters have a cost, resource, or innovation typology, where the reality is a mixture (Seeley, 2011).…”
Section: Data and Proposed Methodsmentioning
confidence: 99%
“…Eco-innovation is a complex process, involving interdisciplinary integration. Therefore, it is very easy for EIE to be impacted by the synthetic influence of many factors [42]. This paper chooses economic level, environmental regulation, innovation capacity, industrial upgrading, and open level as control variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…According to the life cycle theory of agglomeration, agglomeration is a gradual process. In different evolution stages, it has different features, which usually lie in the aspects of the allocation of resources, the establishment of shared facilities, the efficiency of research and development, and the degree of cooperation and competition between enterprises [42]. Therefore, it is very likely that the impacts of manufacturing agglomeration on EIE vary greatly in different evolution stages, that is, the relationship between manufacturing agglomeration and EIE is nonlinear.…”
Section: Introductionmentioning
confidence: 99%